Using Big Books to Foster English Reading Comprehension for Children - nadila, dila; Nuraini, Kristi (Institut Agama Islam Tarbiyatut Tholabah, 2025)
This study explores using Big Books as a pedagogical tool to improve reading comprehension among elementary school students aged 6-12. Big Books, characterized by their large texts and vivid illustrations, create an engaging learning environment that supports vocabulary acquisition, critical thinking, and reading fluency. By synthesizing findings from 15 previous studies from 2010-2024, this study highlights the effectiveness of Big Books in fostering literacy through interactive and enjoyable reading sessions. The results show that the combination of visual aids and textual elements not only attracts students’ attention but also enhances their ability for reading comprehension, improves vocabulary mastery, and can boost students’ self-confidence. In addition, the interactive nature of Big Book sessions can motivate students to participate actively, which enhances engagement and learning outcomes. This paper underscores the importance of integrating Big Books into the English language teaching curriculum to build a strong literacy foundation for young learners.